2018
DOI: 10.1002/jsfa.9153
|View full text |Cite
|
Sign up to set email alerts
|

The role of production process and information on quality expectations and perceptions of sparkling wines

Abstract: It can be concluded that sensory and non-sensory attributes of sparkling wines affect consumers' preferences. Specifically, the study suggests that production process information strongly impacts liking expectations, while not affecting informed liking. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 80 publications
(153 reference statements)
4
33
1
Order By: Relevance
“…The wines were separated into wines that contained fruity attributes (peach, pear, sweet, berry, citrus) or earthy attributes (earthy, floral, bitter, strong, burnt, oak, wood). Previous studies on the sensory aspects of sparkling wines have found that fruit-related attributes are often perceived [32][33][34]. Although earthy attributes are not as commonly used as descriptors, mushroom/earthy characterization has been used before as reference for some sparkling wines [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wines were separated into wines that contained fruity attributes (peach, pear, sweet, berry, citrus) or earthy attributes (earthy, floral, bitter, strong, burnt, oak, wood). Previous studies on the sensory aspects of sparkling wines have found that fruit-related attributes are often perceived [32][33][34]. Although earthy attributes are not as commonly used as descriptors, mushroom/earthy characterization has been used before as reference for some sparkling wines [33].…”
Section: Discussionmentioning
confidence: 99%
“…Although earthy attributes are not as commonly used as descriptors, mushroom/earthy characterization has been used before as reference for some sparkling wines [33]. Another similar categorization previously used would be vegetative-herbaceous [34].…”
Section: Discussionmentioning
confidence: 99%
“…and sensorial profile (taste and aroma; Culbert, Ristic, Ovington, Saliba, & Wilkinson, 2017). Consumers' studies are mostly focused on the purchase, perception and, more recently, there is agrowing attention in how sensorial features affect consumer behavior in general (Vecchio et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They evaluated the effect of wine attributes including still versus sparkling wines. Vecchio et al (2018) figured out that consumers appreciate differently the sparkling production process (Charmat better than Champenoise) while being positively influenced by the brand (Champenoise better than Charmat). Trestini, Giampietri, Szathvary, and Dal Bianco et al (2018) investigated the sparkling wine German market looking at the positioning of Prosecco appellations while checking the consumer perception on Prosecco's appellations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We expect that these variables raise the price of wine. Indeed, from the study conducted by Vecchio et al [34] it emerged that detailed information on the Champenoise, which is just another name for the Traditional method, is perceived as positive and increases WTP especially by young consumers. Brut, Dry and Sweet taste variables are also included to describe attributes.…”
Section: Model Specificationmentioning
confidence: 99%